Monograph on indigenous chicken breeds/ecotypes in Vietnam - Ngo Thi Kim Cuc; Esatu, Wondmeneh; Hoang Hai Hoa; Vu Chi Thien; Nguyen Cong Dinh; Ninh Thi Huyen; Tran Trung Thong; Pham Van Son; Ngo Thi Le Quyen; Unger, Fred; Dessie, Tadelle (International Livestock Research Institute, 2025)
Since mid-2021, the International Livestock Research Institute (ILRI) has partnered with the National Institute of Animal Sciences (NIAS) of Vietnam to conduct research on tropically adapted and high-performance chicken strains under both on-station and on-farm conditions in Vietnam. This collaboration is part of a larger initiative known as the Asian Chicken Genetic Gain (AsCGG) project, which is funded by the Australian Centre for International Agricultural Research (ACIAR) and is still ongoing. The project’s overarching goal is to provide smallholder poultry producers in Vietnam with improved chicken breeds better adapted to the tropical climate, thereby increasing their productivity and sustainability. Vietnam is home to a large genetic diversity of indigenous chickens that are well adapted to its various geographical locations. Indigenous chicken genetic improvement programs in the country have yielded promising results but need to emphasize the maintenance and sustainable use of this genetic diversity. This monograph is an output of the AsCGG project. It describes the Vietnamese indigenous chickens’ phenotypic and genetic characteristics, genetic attributes related to egg and meat production, adaptability of promising chicken ecotypes and their socio-economic contributions. This monograph can be used by researchers, breeders, PhD and master students, NGOs and other practitioners involved in supporting chicken genetic improvement for farmers in the chicken value chain and other actors. This monograph is expected to contribute to capacity building along the value chain, leading to improved chicken genetics. This will enable farmers to transition from backyard or semi-intensive farming to more intensive, market-oriented production, enhancing production, food security and livelihoods while benefiting the wider community and countries involved.